Advances in treatment for postpartum major depressive disorder. (21st September 2020) - Amodeo, Giovanni; Laurenzi, Pier Francesco; Santucci, Aurora; Cuomo, Alessandro; Bolognesi, Simone; Goracci, Arianna; Rossi, Rodolfo; Beccarini Crescenzi, Bruno; Neal, Stephen M; Fagiolini, Andrea
ABSTRACT: Introduction : Postpartum depressive disorder (PPD) is a burdensome medical condition. To date, only one treatment (Brexanolone) has undergone registrational trials and is approved in the United States with an indication for the treatment of PPD. However, other treatments are prescribed and have been tested for this condition. Herein, the authors review the available scientific evidence pertaining to the somatic treatments of PPD. Areas covered : The authors evaluate the published open-label and randomized controlled trials (RCTs), examine the biological mechanisms of PPD treatments, and evaluate how the available data translates into information that may be useful for clinical practice. Expert opinion : Antidepressants have long been the mainstay of PPD treatment, despite the limited evidence from randomized clinical trials that supports this practice. Brexanolone improves treatment options for women with PPD. However, the relatively burdensome administration and monitoring protocol, along with the high cost of the medication, limit the possibility for an extensive use of this medication. Large, randomized, controlled trials of hormonal treatments in patients with PPD are warranted. Also, treatment with mood stabilizers and/or antipsychotics in women with major depressive disorder, who meet the DSM-5 mixed features specifiers in the post-partum period, should be tested in controlled clinical trials.